Displacement and associated substitution behavior among Texas inshore fishing guides due to perceived spotted seatrout declines. (September 2021) - Smith, William E.; Kyle, Gerard T.; Sutton, Steven
Abstract: The objective of this investigation was to investigate displacement behavior among inshore fishing guides based on a contextual self-classification measure reflecting guides' style of participation. Due to a perceived decline of the SST during the 2010 calendar year, significant differences were identified among self-classification categories on two displacement behaviors: (1) substitution of target species for an alternative species, and (2) substitution of primarily used bait and fishing method for an alternative bait or method. The least specialized guide type (Limit Guides) substituted SST for an alternative species more often than All-purpose Guides during the 2010 calendar year. Similarly, Limit Guides also indicated substituting bait or fishing methods for alternatives more often than the most specialized guide group (Sight-casting Guides) during the same time frame. Again, these findings seem reasonable in light of each guide types' contextual style of participation and based on previous research related to specialization and resource substitution. Highlights: A self-classification indicator based on guides' style of participation revealed heterogeneity. Guides reported two displacement behaviors; species targeted and fishing method. Least specialized guides were more inclined to engage in substitution behavior. Reflective of the heterogeneity among anglers, the impact of species decline was not uniform.